Risk management and viability of public organizations. Development of a risk measurement tool: The case of Greece - Iordanis Eleftheriadis; Vasilios Vyttas (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: This paper provides an important contribution towards the development of a valid, reliable and cost-effective instrument that reduces operational and economic risk levels in public sector organizations. Design/methodology/approach: A quantitative methodology based on the collection of primary data via a questionnaire has been adopted in this research. Findings: The research results showed that the measurement tool selected, applied, presented and proposed is comprised of three (3) scales. The reliability analysis proved that all three scales are reliable; therefore, they are suitable for use as a risk measurement instrument. Research limitations/implications: The study's academic contribution is the application and testing of the aforementioned measurement instruments, which can now be utilised by researchers in the field of risk management, to further advance the study of risk management in public organizations in Greece. On the empirical level, the implementation of these three measurement instruments can assist public organizations in Greece via an easy and fast assessment of economic and operational risks. Originality/value : This tool can help public organizations gain insight into the level of risk they face at any given point in time in order plan their actions accordingly. At the same time, central state administration will have the necessary tools to monitor and support the organizations it evaluates.
Keywords: H3; M10; 330; Risk; economic risk; operational risk; Public sector organizations